Investigation of T-cell immunoglobulin- and mucin-domain-containing molecule-3 (TIM-3) polymorphisms in essential thrombocythaemia (ET). Issue 6 (3rd July 2017) - Han, Fuyan; Wang, Guanghai; Li, Yuantang; Tian, Wenjun; Dong, Zhenfang; Cheng, Shiqing; Liu, Yiqing; Qu, Teng; Wang, Xiaoying; Wang, Yong; Zhang, Bingchang; Ju, Ying
ABSTRACT: Objectives: T-cell immunoglobulin- and mucin-domain-containing molecule-3 (TIM-3) is preferentially expressed on terminally differentiated Th1 cells and inhibits their IFN-γ production. It has been reported that chronic inflammation may be an important driving force for myeloproliferative neoplasms (MPNs). Therefore, we hypothesized that as an important inflammation regulator, TIM-3 may be involved in essential thrombocythaemia (ET). The goal of this study was to investigate whether the −1516G > T, −574G > T and +4259T > G single-nucleotide polymorphisms (SNPs) within the TIM-3 gene contribute to the genetic susceptibility of individuals to ET. Methods: Genotyping of the TIM-3 −1516G > T, −574G > T and + 4259T > G SNPs was performed in 175 patients with ET and in 151 controls via a polymerase chain reaction-restriction fragment length polymorphism assay. We also investigated the relationships between the genotypes of each SNP and the risk factors of ET such as routine blood indexes, age and JAK2 V617F mutation. Results: The genotype and allele frequencies of the −1516G > T SNP ( p  = 0.016 and 0.019, respectively), the −574G > T SNP ( p  = 0.035 and 0.038, respectively) and the +4259T > G SNP ( p  = 0.036 and 0.038, respectively) of the ET patients and the controls were significantly different. A haplotype analysis found that the GGT and TGT haplotypes had significantly different distributions between ET and controls ( p  = 0.041 and 0.041, respectively). However, no significant differences were detected between the genotypes of all SNPs and routine blood indexes, age and JAK2V617F mutation. Conclusion: The −1516G > T, −574G > T and +4259T > G SNPs within TIM-3 gene might play an important role as a genetic risk factor in the pathogenesis of ET.